Pengaruh Perencanaan Keuangan terhadap Keberhasilan Wirausahaan - Rama Yanti; Meilina Wiryanada; Yulia Novita; Al Iqram Septari (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of financial planning on the business success of young entrepreneurs. Financial planning plays a vital role in guiding entrepreneurs in allocating resources, determining spending priorities, projecting future financial conditions, and minimizing financial risks. Many young entrepreneurs face difficulties in maintaining business stability due to limited experience in managing budgets, controlling cash flow, and making strategic financial decisions. This research employs a quantitative approach using a survey method with a structured questionnaire distributed to young entrepreneurs from various business sectors. The collected data were processed using multiple linear regression to examine the magnitude of the effect of budget planning, cash flow control, and financial forecasting on business performance. The results show that financial planning has a significant and positive effect on business success, where better planning encourages improved operational efficiency, profit growth, and business continuity. This finding implies that young entrepreneurs must develop structured financial planning skills to improve their competitive advantage. This study highlights that financial planning is not only a technical activity but also a strategic tool that determines long term business sustainability.